A nationwide pharmacovigilance investigation on trends and seriousness of adverse events induced by anti-obesity medication - Choi, Yeo Jin; Choi, Chang Young; Kim, Choong Ui; Shin, Sooyoung (Journal of Global Health, 2023)
Introduction Despite rising concerns regarding the safety of anti-obesity medications, there is a lack of comprehensive pharmacovigilance investigations utilising real-world data. We aimed to characterise the prevalence and seriousness of adverse drug events (ADEs) related to anti-obesity medications and to identify predictors associated with increased risk of serious adverse events (SAE), thereby conveying evidence on drug safety. Methods We conducted a cross-sectional analysis on ADE cases spontaneously reported to the Korea Adverse Event Reporting System Database (KIDS-KD). ADE reports pertaining to anti-obesity medications prescribed for overweight, obesity (International Classification of Disease, 10th revision (ICD-10) code E66) and abnormal weight gain (ICD-10 code E63.5) were included in the analysis. We performed a disproportionality to detect the association of the system organ class-based ADEs with their seriousness an individual’s sex by estimating reporting odds ratios (RORs) and their 95% confidence intervals (CIs). We performed logistic regression to investigate factors that are substantially associated with increased SAE risks by estimating odds ratio (OR) and their 95% CIs. Results The most common causative anti-obesity medication was phentermine, followed by liraglutide. ADEs associated with psychiatric disorders (ROR=1.734; 95% CI=1.111-2.707), liver and biliary system disorders (ROR=22.948; 95% CI=6.613-70.635), cardiovascular disorders (ROR=5.707; 95% CI=1.965-16.574), and respiratory disorders (ROR=4.567; 95% CI=1.774-11.762) were more likely to be serious events. Additionally, men are more likely to experience ADEs related gastrointestinal disorders (ROR=1.411) and less likely to have heart and rhythm disorders (ROR=0.507). The risk of SAE incidences was positively correlated with being male (OR=2.196; 95% CI=1.296- 3.721), dual or triple combination of anti-obesity medications (OR=3.258; 95% CI=1.633-6.501 and OR=8.226; 95% CI=3.046-22.218, respectively), and concomitant administration of fluoxetine (OR=5.236; 95% CI=2.218-12.365). Conclusions Seriousness of anti-obesity medication-related ADEs differs among system-organ class, while sex-related differences in ADE profiles are also present. The predictors substantially increasing risk of SAE incidences include being male, having a higher number of concomitant medications (including multiple combination of anti-obesity medications), and concurrent use of fluoxetine. Nonetheless, further pharmacovigilance investigation and monitoring are needed to enhance awareness on ADEs induced by anti-obesity medications.
Keywords: Cardiovascular Diseases; Cross-Sectional Studies; Female; Fluoxetine; Humans; Male; Obesity; Pharmacovigilance